RETENSI MODAL PENGETAHUAN DAN SUMBERDAYA INTERNAL PERUSAHAAN - Agustian Budi Prasetya (ITB AAS INDONESIA, 2017)
The paper discuss about retention model of corporate knowledge capital and identification internal resources that affect the efectivity of retention of corporate knowledge capital. The research utilize desk research methodes, based on academic literaturs. The paper describe analytically the DeLong and Arif et.all of knowedge retention model, apply with retention cases. The paper found that along with effort to keep the corporate capital knowledge, company might face threat of loosing the knowledge, the capacity to make decision effectively due to the mismanagement of company internal resurces, such as: staffing, turnover, recruitment, eangement to type of short term project; weak leadership and prioritizing; ineffective of information technology management. Key words : knowledge retention, corporate knowledge capital, company internal resources, loss of knowledge